The Mechanism on the Acupuncture Treatment of Type 2 Diabetes - Wong, Connie Hsuah Nee (2015)
Type 2 diabetes mellitus are quite common among the public in modern society. However, there is no cure for diabetes mellitus, most of the patients need to take life-long medication to prevent complication due to type 2 diabetes mellitus. That is why the prevention of diabetes mellitus become important, identify the potential type 2 diabetes group of people decrease their possibilities to proceed to type 2 diabetes mellitus patients. Understanding the pathogenesis of type 2 diabetes mellitus in Chinese Medicine to find out the cause of type2 diabetes mellitus and prevent it through acupuncture treatment.